Teleproctoring for Neurovascular Procedures: Demonstration of Concept Using Optical See-Through Head-Mounted Display, Interactive Mixed Reality, and Virtual Space Sharing—A Critical Need Highlighted by the COVID-19 Pandemic - Rai, A.T.; Deib, G.; Smith, D.; Boo, S. (American Journal of Neuroradiology, 2021)
BACKGROUND AND PURPOSE: Physician training and onsite proctoring are critical for safely introducing new biomedical devices, a process that has been disrupted by the pandemic. A teleproctoring concept using optical see-through head-mounted displays with a proctor's ability to see and, more important, virtually interact in the operator's visual field is presented.MATERIALS AND METHODS: Test conditions were created for simulated proctoring using a bifurcation aneurysm flow model for WEB device deployment. The operator in the angiography suite wore a Magic Leap-1 optical see-through head-mounted display to livestream his or her FOV to a proctor's computer in an adjacent building. A Web-based application (Spatial) was used for the proctor to virtually interact in the operator's visual space. Tested elements included the quality of the livestream, communication, and the proctor's ability to interact in the operator's environment using mixed reality. A hotspot and a Wi-Fi-based network were tested.RESULTS: The operator successfully livestreamed the angiography room environment and his FOV of the monitor to the remotely located proctor. The proctor communicated and guided the operator through the procedure over the optical see-through head-mounted displays, a process that was repeated several times. The proctor used mixed reality and virtual space sharing to successfully project images, annotations, and data in the operator's FOV for highlighting any device or procedural aspects. The livestream latency was 0.71 (SD, 0.03) seconds for Wi-Fi and 0.86 (SD, 0.3) seconds for the hotspot (P = .02). The livestream quality was subjectively better over the Wi-Fi.CONCLUSIONS: New technologies using head-mounted displays and virtual space sharing could offer solutions applicable to remote proctoring in the neurointerventional space.COVID-19coronavirus disease 2019OST-HMDoptical see-through head-mounted display